Upaya Peningkatan Kebutuhan Nutrisi Kurang Dari Kebutuhan Tubuh Pada Pasien Anak Dengan Demam Thypoid Di Rawat Inap Puskesmas Kartasura - Pambudi, Dimas Agung; , Dian Nur Wulanningrum, S.Kp., Ns., M.Kep (2017)
Introduction: Typhoid fever is an acute infectious disease a public health problem in developing countries, especially tropical countries, caused by salmonella typhi. The disease infects the gastrointestinal tract. The disease is transmitted through water and food contaminated by the bacteria Salmonella typhi common in school age (5-15 years). The most severe incidence of typhoid fever is death. Nutrition less than body requirements is one of the problems that arise. School age shows the range of disease typhoid fever due to environmental factors that affect eating patterns. The general objective of knowing and implementing nutritional needs in children with typhoid fever according to the standard of nursing. Special Purpose identifies priorities for nursing diagnosis, nursing plan, perform an act in accordance with the care plan, and evaluate nursing actions. Methods: A case study approach through interviews and observations of medical records resulting data to support. Results: From all the studies and data that supports that generates diagnoses nursing, nutritional imbalance is less than the needs of the body that becomes an important issue. Discussion: Having done during the 3x8-hour nursing actions that meet the needs of nutrients needed so the problem of lack of nutrients can be resolved. Conclusion: Meeting the nutritional needs of patients with typhoid fever is very important so that the intake of nutrients to the body's metabolism is fulfilled and does not cause a more severe disorder. Keywords: typhoid fever, nutrition, school age